Characterizing Changes from a Century of Genetic Improvement of Soybean Cultivars in Northeast China. Issue 5 (1st September 2015) - Wu, Tingting; Sun, Shi; Wang, Caijie; Lu, Wencheng; Sun, Bincheng; Song, Xiqing; Han, Xiaozeng; Guo, Tai; Man, Weiqun; Cheng, Yanxi; Niu, Jianguang; Fu, Lianshun; et al.
ABSTRACT: The first soybean [ Glycine max (L.) Merr.] breeding program in China was established in the northeast in 1913. A trend analysis of widely grown cultivars across Chinese soybean breeding history may provide a better perspective on the genetic progress in soybean. The objective of the current study was to assess the genetic change of 15 phenological, yield, and agronomic traits on widely grown cultivars in northeast China. Sixty‐four soybean cultivars representing a span of 84 yr (1923–2007) of release were included. The field experiments were conducted at three sites in each region during 2009, 2010, and 2011, and the annual genetic changes were obtained by regression analysis. The results showed that the yield gain in widely grown cultivars of different regions ranged from 6 to 16 kg ha −1 yr −1 due to improvements in different yield components in the last nine decades. In addition, modern cultivars demonstrated more upright plant architecture, fewer branches, shorter height, higher lodging resistance, and earlier flowering than obsolete cultivars. However, changes were insignificant in the height of the bottom pod and the node number. The changing rates of yield and phenological traits across these decades were constant, while that of agronomic traits were discontinuous. Days to flowering, branch number, and lodging score were more responsive to environments in new cultivars than in old cultivars. In conclusion, these findings indicate a substantial improvement in the yield, agronomic, and phenological traits resulted from long‐term genetic breeding. This study also provides insight into developing new strategies for soybean genetic improvement in China and worldwide.